Estimating Optimum Amount of Stock in The Warehousing Process Using Newsvendor Model - Fania, Farell; Damayanti , Dida Diah; Sumargo, Seto (eProceedings of Engineering, 2024)
PT Grow Commerce Indonesia is a technologydriven company which focuses on the digital branding ofpartner brands, mostly local brands. They also help in thewarehouse and distribution activities of the partner brand’sproducts. The warehouses that are used by Grow Commerce arethe partner brands. The problem faced by PT. Grow CommerceIndonesia is that each year, their warehouse always hasoverstock left, with increase of quantity each year. The authorintends to analyze the problem and design a solution using theNewsvendor Model. The Newsvendor model helps indetermining the optimum quantity of products that should bemanufactured/ordered to avoid overstocking (supply is morethan demand) and or understocking (demand is more thansupply) which overall avoids the loss of profit. By analyzing theforecast of demands, the Newsvendor model can calculate theoptimum number of stocks to minimize loss of profit. Keywords— PT. Grow Commerce Indonesia, Overstock,Newsvendor Model